2018
DOI: 10.3126/jmcjms.v6i1.20575
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of Metacarpal Fracture managed with Miniplate and Screws

Abstract: Background and Objectives: Early techniques of splint immobilization work well for simple metacarpal fractures. However, if significantly shorting, rotational deformity, and angulations occur, surgical treatment is required. The aim of this article was to study the functional outcome of metacarpal fractures treated by open reduction and internal fixation with mini plates and screw in low resource condition of Nepal.Material and Methods: This retrospective study was done over a period of one year 2012 to 2013 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These findings are similar to those reported by other authors. 31,32,33 Brown concluded that spiral fractures gave satisfactory results, while oblique fractures had less satisfactory results. 34 Rigid internal fixation of the metacarpal fractures allowed early active hand motion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those reported by other authors. 31,32,33 Brown concluded that spiral fractures gave satisfactory results, while oblique fractures had less satisfactory results. 34 Rigid internal fixation of the metacarpal fractures allowed early active hand motion.…”
Section: Discussionmentioning
confidence: 99%